The impact of foreign bank entry in emerging markets: Evidence from India - Gormley, Todd A. (Journal of Financial Intermediation, 2010)
This paper uses the entry of foreign banks into India during the 1990s—analyzing variation in both the timing of the new foreign banks’ entries and in their location—to estimate the effect of foreign bank entry on domestic credit access and firm performance. In contrast to the belief that foreign bank entry should improve credit access for all firms, the estimates indicate that foreign banks financed only a small set of very profitable firms upon entry, and that on average, firms were 8 percentage points less likely to have a loan after a foreign bank entry because of a systematic drop in domestic bank loans. Similar estimates are obtained using the location of pre-existing foreign firms as an instrument for foreign bank locations. Moreover, the observed decline in loans is greater among smaller firms, firms with fewer tangible assets, and firms affiliated with business groups. The drop in credit also appears to adversely affect the performance of smaller firms with greater dependence on external financing. Overall, this evidence is consistent with the exacerbation of information asymmetries upon foreign bank entry.